2022
DOI: 10.1002/hsr2.492
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the peripheral blood T and B cell subsets and IRF‐7 variants in adult patients with severe influenza virus infection

Abstract: Background and Aims Influenza virus is one of the leading infections causing death among human being. Despite known risks, primary immune deficiency due to Interferon Regulatory Factor‐7 (IRF7) gene defect was reported as a possible cause of the risk factors for complicated influenza. We aimed to investigate the changes in peripheral T and B cell subsets in adult patients with severe seasonal influenza virus infection and the investigation of variants of IRF7 gene. Methods In this study, 32 patients, hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This suggests a differentiation toward more effector-like T cell populations with acute infection, which is not unexpected given observations of T cell differentiation in viral infection models ( 17 , 18 ). It also fits with a previous study showing increases in memory T cell subsets and decrease in naive T cells in hospitalized adults with influenza ( 12 ). The reduced frequency of regulatory T cells in young infected individuals could indicate a shift from an anti-inflammatory to an inflammatory response to infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests a differentiation toward more effector-like T cell populations with acute infection, which is not unexpected given observations of T cell differentiation in viral infection models ( 17 , 18 ). It also fits with a previous study showing increases in memory T cell subsets and decrease in naive T cells in hospitalized adults with influenza ( 12 ). The reduced frequency of regulatory T cells in young infected individuals could indicate a shift from an anti-inflammatory to an inflammatory response to infection.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, previous studies have made observations on certain cell populations in a limited range of individuals. For example, one study showed increases in central and effector memory T cell populations, with a concomitant decrease in naive T cells, in hospitalized adults with acute influenza ( 12 ). Another study showed decreases in total T and NK cell counts in children hospitalized with acute influenza ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high level of inflammatory cytokines and excessive infiltration of neutrophils and macrophages [ 24 ] can suppress adaptive immune response, and cause activation-induced cell death (AICD) of lymphocytes, which results in lymphopenia. The exhausted lymphocytes lose their activation, proliferation, differentiation and antiviral ability, and lead to virus evasion [ 28 , 29 ]. Clinical evidences have shown that lymphopenia in peripheral blood is common at the early stage of respiratory virus infection [ [29] , [30] , [31] , [32] ], which often predicts a poor prognosis and even death [ 29 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exhausted lymphocytes lose their activation, proliferation, differentiation and antiviral ability, and lead to virus evasion [ 28 , 29 ]. Clinical evidences have shown that lymphopenia in peripheral blood is common at the early stage of respiratory virus infection [ [29] , [30] , [31] , [32] ], which often predicts a poor prognosis and even death [ 29 , 33 ]. Proportion of immune cells infiltrated in lung tissue in our experiments showed that SFJDC reduced the proportion of neutrophils and macrophages, while increasing the proportion of T and B cells.…”
Section: Discussionmentioning
confidence: 99%